A Subtitling Analysis Of Noun Phrases In Fast And Furious 6 Movie By Geraldine - Eksanusi, Ardi, Dr. Dwi Haryanti, M.Hum, Siti Fatimah, S. Pd, M. Hum (2015)
This study aims at describing the subtitling analysis of noun phrase from English into Indonesia in Fast and Furious 6 movie, classify the translation shifts of noun phrase found in Fast and Furious 6 movie and describe the translation equivalence of the subtitled. The type of this research is descriptive qualitative research. In collecting data, the writer uses documentation. The data are analyzed using translation analysis theory based on A Linguistic Theory of Translation by Catford (1965). There are steps of collecting data, namely: the writer watching the movie and findings the noun phrase on the dialogue occur the movies, noting the script, classifying the noun phrase, coding the data of noun phrases. The collected data are analyzed by using A Linguistic Theory of Translation by Catford. The result of the research show that the writer found 281 data of noun phrases that using translation shift in Fast and Furious 6 movie. The writer classify translation shift into two types. There are level shift and structural shift. It consist of 156 data or 55% of noun phrases belong to level shifts and 125 data or 45% of noun phrases belong to structural shifts. From 281 data of noun phrases, the writer finds that all of the data of noun phrases are equivalent translation and the writer does not finds any data of noun phrases included in not equivalent translation. It means that the data is 100% equivalent. The result of this study is that the translator makes an equivalent translation.